Core muscle activation during stand-up paddleboarding in comparison to treadmill running - Vogel, Autumn R. (My University, 2016)
The main purpose of this study was to determine if the core muscles are sufficiently activated to provide strength benefit during stand-up paddleboarding (SUP). A secondary purpose was to compare activation of the core muscles during SUP to treadmill running. Thirteen subjects performed SUP and treadmill (1M) running at RPE's of 11, 13, and 15. Surface electromyography (EMG) was recorded for the external oblique (EO), rectus abdominus (RA), erector spinae (ES), latissimus dorsi (LD), gluteus maximus (GM), and vastus lateralis (VL). Electromyography between the two conditions was compared using a two-way ANOV A with repeated measures. Significance was found between the muscles using a Fisher's LSD postRhoc test. The results of this study indicate that training at a moderate to vigorous intensity on SUP can activate the EO, RA, LD, and ES musculature. Therefore, SUP can be recommended to people looking to train and strengthen core musculature and the LD. However, SUP does not provide sufficient activation to the VL and GM muscles. Treadmill running would be the preferred method to train these muscles.
Keywords: Treadmill exercise tests; Exercise--physiological aspects; Kinesiology